2012
DOI: 10.1088/1009-0630/14/2/13
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Migration of Diethylhexyl Phthalate in Functional PVC Films

Abstract: Plasticizers that are generally used in plastics to produce flexible food packaging materials have proved to cause reproductive system problems and women's infertility. A longterm consumption may even cause cancer diseases. Hence a nano-scale layer, named as functional barrier layer, was deposited on the plastic surface to prevent plasticizer diethylhexyl phthalate's (DEHP) migration from plastics to foods. The feasibility of functional barrier layer i.e. SiOx coating through plasma enhanced chemical vapor dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…observed that the migration of phthalates in beverages is accelerated in acid medium (pH < 5) by modifying the structure of the plastic polymer. Similar reports showed that migration of phthalates increases with temperature, contact time, dry matter content and hydrophobic nature of food [ 22 , 23 , 15 , 19 ]. On contrary, studies show that the successive washing of plastic containers contributes to reduce the content of additives that they release, due to the depolymerisation of the polymer [ 24 , 25 ].…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…observed that the migration of phthalates in beverages is accelerated in acid medium (pH < 5) by modifying the structure of the plastic polymer. Similar reports showed that migration of phthalates increases with temperature, contact time, dry matter content and hydrophobic nature of food [ 22 , 23 , 15 , 19 ]. On contrary, studies show that the successive washing of plastic containers contributes to reduce the content of additives that they release, due to the depolymerisation of the polymer [ 24 , 25 ].…”
Section: Introductionsupporting
confidence: 64%
“…[ 16 , 17 , 18 , 19 ]. There is an evidence that the migration of phthalates is high in fatty food than is acid or aqueous food [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantage of these techniques is the long treatment time, from tens of minutes to hours . The treatment of the PVC with a low pressure plasma also leads to reduction of plasticizer migration . Drawbacks of the low pressure process are long evacuation times, due to the presence of volatile components in the polymer, as well as the difficulty to achieve the material treatment continuously in in‐line processing.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] The treatment of the PVC with a low pressure plasma also leads to reduction of plasticizer migration. [23][24][25][26] Drawbacks of the low pressure process are long evacuation times, due to the presence of volatile components in the polymer, as well as the difficulty to achieve the material treatment continuously in in-line processing. Barreto et al [27] studied the protective coating of organosilicon compounds (HMDSO, OMCTS) using dielectric barrier discharge in nitrogen .…”
mentioning
confidence: 99%